Formulation and characterization of voriconazole nanospray dried powders. (8th August 2020) - Chen, Rui; Zhang, Tinghua; Bao, Sha; Liu, Yinkun; Xu, Xiaohong
Abstract: Purpose: Voriconazole nanoparticles (API-NPs) were prepared by nanospray drying to improve the solubility of voriconazole and reduce its interindividual variability. Methods: The preparation procedure was optimized by central composite design-response surface methodology. The properties of the nanoparticles were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) analyses. The solubility, dissolution, and stability of the API-NPs were determined experimentally. The pharmacokinetics were assessed based on rat plasma levels of voriconazole. An acute oral toxicity test of the API-NPs was performed in mice. Results: The powers were formulated using cetyltrimethylammonium chloride (CTAC) as the carrier material. SEM and particle size results showed that the API-NPs had a narrow particle size distribution. The XRD, DSC, and FTIR analyses show a decrease in crystallinity and a polymorphic transformation of the nanoparticles after nanospray drying. The solubility in water was approximately 15 times higher than that of voriconazole. The API-NP tablets exhibited significantly higher plasma exposure, namely, longer acting times and lower variability. The acute administration of voriconazole showed no toxic histopathological effects on organ tissue. Conclusion: The solubility of voriconazole was greatly improved, it showed higher bioavailability and safety, and the interindividual variability in voriconazole pharmacokinetics was reduced by nanospray drying.